Direct Anticoagulants and Risk of Myocardial Infarction, a Multiple Treatment Network Meta-Analysis - Kupó Péter (ANGIOLOGY, 2019)
We assessed the cardiovascular safety of long-term direct-acting oral anticoagulant (DOAC) treatment. A search of the medical literature was performed from inception until May 31, 2019. Inclusion criteria were (1) randomized trial that assessed the clinical efficacy and/or safety of 1 or more DOAC, (2) control group including oral anticoagulation and/or antiplatelet and/or placebo treatment, and (3) the incidence of acute coronary syndrome during follow-up was reported. Fixed-effect and random-effects models were applied. The analyzed outcomes were myocardial infarction (MI), major bleeding, and mortality. Twenty-eight randomized clinical trials (196 761 patients) were included. Rivaroxaban was associated with a 21% reduction in the relative risk of MI when compared to placebo (relative risk [RR]: 0.79 [95% credible interval, CrI: 0.65-0.94]) and a 31% reduction (RR: 0.70 [95% CrI: 0.53-0.89]) when compared to dabigatran. Apixaban resulted in 24% (RR: 0.76 [95% CrI: 0.58-0.99]) and vitamin K antagonists anticoagulation resulted in 19% (RR: 0.81 [95% CrI: 0.65-0.98]) risk reduction compared to dabigatran. The computed probability of being the first best choice of treatment was 61.8% for rivaroxaban. Cardiovascular safety shows considerable heterogeneity among oral anticoagulants. Treatment with rivaroxaban is associated with reduced rate of MI.